Facilitation of small business development as a means of combating labour migration - Lukashova, Liudmyla (Technium Social Sciences Journal, 2020)
The undeniable relevance of the research stems from the intensification of the migration crisis in Ukraine and the increase in the number of migrant workers to 100 thousand people per month. The main trends, causes and consequences of labour migration from Ukraine prove the need to find new tools that can prevent an increase in the flow of migrant workers. The object of the study is the process of facilitating small business development, which is considered as a priority means of combating labour migration in Ukraine. The practical value of the obtained research results lies in the possibility of their application in the Ukrainian realities and the solution of the migration crisis problem by improving the economic conditions of the most mass stratum of business entities. The list of facilitation and deregulation measures for small business entities formed on the basis of diagnostics of the current legal framework allowed to conduct a critical reforms analysis, identify "bottlenecks" and problems of legislative implementation. The author verified that the provision of financial and credit support to small business entities under the soft loan program is feasible only if quality monitoring of the targeted use of funds is provided. Due to the calculations, the size of an additional limiting parameter to the applicants' business plans was determined, in particular, the return on capital investment of not less than 10%. Thus, the need for this percentage entails the lack or insufficient quality of monitoring.